2011
DOI: 10.1158/1940-6207.capr-11-0298
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Prospective Randomized Trial of a Low-Fat Diet with Fish Oil Supplementation in Men Undergoing Radical Prostatectomy

Abstract: Preclinical studies suggest lowering dietary fat and decreasing the ratio of omega-6 to omega-3 polyunsaturated fatty acids decreases the risk of prostate cancer development and progression. We conducted a phase II randomized trial to test the effect of decreasing dietary fat combined with decreasing the dietary omega-6:omega-3 ratio on biomarkers related to prostate cancer development and progression. Patients undergoing radical prostatectomy were randomly assigned to receive a low-fat diet with 5 grams of fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 47 publications
1
64
2
Order By: Relevance
“…Although the analysis of patients consuming supplements has greater potential for bias (which is why we excluded them from the main analysis), it does support the protective effect of EPA in the target tissue (prostate). It has already been shown that w-3 fatty acid supplementation increases the w-3 fatty acid content of prostate tissue in specimens of prostatectomy (41,42). These observations combined with our new results suggest a potential protective effect of w-3 fatty acid supplements on prostate cancer carcinogenesis.…”
Section: Discussionsupporting
confidence: 82%
“…Although the analysis of patients consuming supplements has greater potential for bias (which is why we excluded them from the main analysis), it does support the protective effect of EPA in the target tissue (prostate). It has already been shown that w-3 fatty acid supplementation increases the w-3 fatty acid content of prostate tissue in specimens of prostatectomy (41,42). These observations combined with our new results suggest a potential protective effect of w-3 fatty acid supplements on prostate cancer carcinogenesis.…”
Section: Discussionsupporting
confidence: 82%
“…Our result on green tea effect is consistent with a clinical trial of ninety-three men who completed the intervention of 6 cups/day brewed green and black tea prior to prostatectomy, which showed no significant effect of tea consumption on Ki-67 level in prostatectomy tissues (49). However, our non-significant finding of fish oil supplementation is not consistent with a clinical trial of low-fat diet with fish oil supplementation among men undergoing radical prostatectomy, which showed a significant decreased tumor tissue Ki-67 level (45) in the intervention group. This suggests that should the alteration of FAS expression slow prostate cancer development or progression it may not function by altering cell proliferation in non-malignant tissue.…”
Section: Discussioncontrasting
confidence: 99%
“…Compared to an Italian study which showed a significant chemoprevention effect of green tea catechins (GTC) on prostate cancer (44), our study’s intervention doses (EGCG 600mg) were similar to the GTC study (600 mg); but our intervention period (12–20 weeks) was much short than the GTC study (1 year). Compared to a clinical trial showing a 4–6 week low-fat diet with fish oil supplementation (1g EPA+ 1.8g DHA) intervention could significantly decrease prostate tissue Ki-67 level (45), our fish oil doses (1.9g EPA+DHA) were lower. The shorter duration or lower doses may restrict our ability to discern an effect of supplementation on FAS or Ki-67 expression, especially if the variation in FAS or Ki-67 protein expression caused by fish oil or green tea supplementation is a cumulative effect.…”
Section: Discussionmentioning
confidence: 73%
“…This might be probably due to the higher baseline serum IGF1 levels in prostate cancer patients unlike CVD patients participated in the present study [15,16]. Burned patients on the other hand showed a better recovery of decreased serum IGF1 levels after fish oil supplementation.…”
Section: Discussionmentioning
confidence: 74%